A daily regimen of a ceramide‐dominant moisturizing cream and cleanser restores the skin permeability barrier in adults with moderate eczema: A randomized trial. Issue 4 (24th May 2021) - Spada, Fabrizio; Harrison, Ian P.; Barnes, Tanya M.; Greive, Kerryn A.; Daniels, Daisy; Townley, Joshua P.; Mostafa, Niyaz; Fong, Andrew T.; Tong, Philip L.; Shumack, Stephen
Abstract: The dysfunctional skin barrier in eczema patients may be attributed to decreased levels of ceramides in the stratum corneum. The aim of this study was to determine whether a two‐part system consisting of a ceramide‐dominant physiological lipid‐based moisturizing cream and cleanser could ameliorate the signs and symptoms of moderate eczema in adults over 28 days compared to placebo. Assessments were conducted at baseline and every 7 days thereafter. Eczema area severity index score decreased significantly across all time points in both groups compared to baseline ( P < .0001), however, this decrease was not significant between groups at day 28 ( P = .7804). In contrast, transepidermal water loss and skin hydration significantly improved over time in the active group, while it either stayed the same or worsened in the placebo group ( P = .0342 and P < .0001, respectively). There was no difference in the use of mometasone furoate as rescue medication over time between groups ( P = .1579). Dermatology life quality index scores improved significantly in both groups ( P < .0001), with no difference between groups ( P = .5256). However, patient satisfaction was greater in the active compared to the placebo group for several parameters including relief of itch, dry skin, skin softness and smoothness (all P < .05). No patients withdrew from the study due to adverse events (AEs) and there were no serious AEs. The ceramide‐dominant moisturizing cream and cleanser safely restores skin permeability and improves the signs and symptoms of eczema in adults.